1995
DOI: 10.1111/j.1741-6248.1995.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Life After Succession in the Family Business: Is It Really the End of Problems?

Abstract: The succession processes in family business are well chronicled in the business literature. Most of the research focuses on the process of transferring power within the business-family. What has not been as closely examined is the after-succession environment that exists when the management and leadership of the family business are passed on to the next generation. This article addresses that organizational climate and the potential for additional problems in the business-family if post-succession issues are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 27 publications
2
41
0
3
Order By: Relevance
“…New opportunities must be explored and new business practices introduced. The cases showed that the successors had to establish their leadership, overcoming the problems and conflicts that accompany succession that are reported by Harvey and Evans (1995). In the Chinese firms, it appears that the successors must assume the central entrepreneurial role that their predecessors occupied.…”
Section: Discussionmentioning
confidence: 99%
“…New opportunities must be explored and new business practices introduced. The cases showed that the successors had to establish their leadership, overcoming the problems and conflicts that accompany succession that are reported by Harvey and Evans (1995). In the Chinese firms, it appears that the successors must assume the central entrepreneurial role that their predecessors occupied.…”
Section: Discussionmentioning
confidence: 99%
“…Central to many literature reviews is the notion that the quality of the relationship between the outgoing leader and the successor is a critical determinant of the success of the succession process (Brockhaus, 2004, p. 169; Chrisman, Chua, & Sharma, 1998, p. 19; Dickinson, 2000, p. 70; Lansberg & Astrachan, 1994, p. 40). A high‐quality relationship is characterized by a high level of trust, mutual support, open and earnest communication, and the willingness to acknowledge each other's achievements (Harvey & Evans, 1995, p. 10; F. Neubauer & Lank, 1998, p. 142).…”
Section: The Successor‐related Factors That Influence Successionmentioning
confidence: 99%
“…Goldberg (1996, p. 186), Harvey and Evans (1995, p. 12), and Hume (1999, p. 22) point out that not only the satisfaction of various stakeholders with the succession process defines a successful succession, but also the successor's ability to keep the family business healthy by means of sustained growth and continued profitability. Santiago (2000, p. 20), taking a more holistic view, argues that if the leadership transition was so smooth that the change did not disrupt the family or the business, then the succession could be labeled highly successful.…”
Section: The Successor‐related Factors That Influence Successionmentioning
confidence: 99%
“…The little empirical research on this subject yields conflicting findings. Some researchers argue that succession has disruptive and often negative consequences for an organization in terms of conflict (Gouldner, 1954;Grusky, 1960;Harvey & Evans, 1995), whereas other researchers (e.g., Guest, 1962) suggest the oppositenamely, that succession may actually reduce conflict. However, as yet, there are no explicit studies examining the impact of the continued presence of the founder postsuccession on organizational conflict in the family firm.…”
Section: Introductionmentioning
confidence: 99%